2014
DOI: 10.5606/tjr.2014.4590
|View full text |Cite
|
Sign up to set email alerts
|

Grip Ability Test in Rheumatoid Arthritis Patients: Relationship With Disease Activity and Hand-Specific Self-Report Questionnaires

Abstract: Objectives:The aim of this study was to investigate the relationship between the Grip Ability Test (GAT) and disease activity, and hand-specific self-report questionnaires in patients with rheumatoid arthritis (RA). Patients and methods:The study included 65 RA patients (55 females, 10 males; mean age 55±11 years; range 24 to 74 years) who were diagnosed according to the American College of Rheumatology/European League Against Rheumatism 2010 criteria. Duration of disease and duration of morning stiffness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Moreover, GAT was prolonged among RA hands. Current study results were matching with Bircan et al's [21] and Verma and his colleagues' [4] studies where GAT scores were seen affected in 95 % of the studied RA patients. These findings were in agreement with the findings of Silva et al [22] who found that the handgrip strength was weak among the patients with RA compared with the controls.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, GAT was prolonged among RA hands. Current study results were matching with Bircan et al's [21] and Verma and his colleagues' [4] studies where GAT scores were seen affected in 95 % of the studied RA patients. These findings were in agreement with the findings of Silva et al [22] who found that the handgrip strength was weak among the patients with RA compared with the controls.…”
Section: Discussionsupporting
confidence: 90%
“…Hand dynamometer was used as an accurate method for assessment of HGS in normal children [7,8]. Among adults with rheumatoid arthritis (RA), studies suggested that HGS measured by dynamometer being a routine evaluation in these patients [9], and can be used as a measure for disease activity in patients with RA [10][11][12]. Evaluating HGS either subjectively or objectively in children with different rheumatic diseases including JIA has been previously studied [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The articles in the review were based on 19 independent studies of people with RA. Fifteen of the 20 articles (75%) were cross‐sectional , 2 were case‐control , and 3 were cohort studies . Case‐control and cohort studies included in this review presented cross‐sectional data on the association between factors and hand function, therefore all studies were considered to be cross‐sectional, resulting in limited evidence in the best‐evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…After 4 consensus meetings, no disagreement persisted, and a third reviewer was not required to achieve consensus. Overall quality, assessed by the reviewers as the total percentage of quality appraisal items endorsed for each study, was high (≥60%) for 5 studies (25%) . The mean quality score for the 20 included articles was 49.5% (range 25–75%).…”
Section: Resultsmentioning
confidence: 99%